Improving understanding of disease control implementation research through a mooc with participants from low- and middle-income countries: Evaluating participant reactions and learning. - Adanna Nwameme; Phyllis Dako-Gyeke; Emmanuel Asampong; Pascale Allotey; Daniel D Reidpath; Edith Certain; Mahnaz Vahedi; Bella Ross; Dermot Maher; Pascal Launois (Public Library of Science (PLoS), 2023)
The Special Programme for Research and Training in Tropical Diseases developed a massive open online course (MOOC) on implementation research with a focus on infectious diseases of poverty (IDPs) to reinforce the explanation of implementation research concepts through real case studies. The target MOOC participant group included public health officers, researchers and students. By reshaping institutions and building resilience in communities and systems, implementation research will allow progress towards universal health coverage and sustainable development goals. This study evaluates learners' knowledge in implementation research after completing the MOOC using anonymous exit survey responses. Of the almost 4000 enrolled in the two sessions of the MOOC in 2018, about 30% completed all five modules and the assessments, and were awarded certificates. The majority of the participants were early to mid-career professionals, under the age of 40, and from low- and middle-income countries. They were slightly more likely to be men (56%) with a Bachelor or a Master's degree. Participants were public health researchers (45%), public health officers (11%) or students (11%). On completion of the course, an exit survey revealed that 80.9% of respondents indicated significant improvement to strong and very strong implementation research knowledge. This evaluation clearly shows the usefulness of the MOOC on implementation research for reaching out to field researchers and public health practitioners who are facing problems in the implementation of control programmes in low- and middle-income countries.